THE SECRET OF THE MYSTERIOUS STAR (ABOUT UTKIR HOSHIMOV’S STORY “MYSTERIOUS STAR”) - Shahlo Hojieva; Gulnora Tadjieva (Scholar Express Journal, 2022)
This article discusses the role of the People's Writer of Uzbekistan Utkir Hoshimov in Uzbek storytelling. The story of the “Mysterious Star” illustrates the writer's unique skill and method of depiction
Keywords: prose; pandnoma bitik; consciousness; national spirit